2012
DOI: 10.1111/j.1095-8649.2012.03300.x
|View full text |Cite
|
Sign up to set email alerts
|

Feeding ecology of the American freshwater goby Ctenogobius shufeldti (Gobiidae, Perciformes) in a sub‐tropical estuary

Abstract: The feeding ecology of the American freshwater goby Ctenogobius shufeldti in a low salinity salt-marsh habitat in the Paranaguá Bay estuarine complex (Brazil) was assessed through the gut analysis of 632 individuals. The effects of a set of abiotic factors (type of sediment, salinity, temperature and estuarine reach), season and body size on dietary composition were analysed. Seasonal and size-related changes in feeding strategy, feeding intensity and trophic level were assessed. The effects of gape and body s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 41 publications
0
9
0
3
Order By: Relevance
“…Previous research on goby ( Ctenogobius sp.) diet indicated that the most important prey items were diatoms growing on seagrass leaves or mudflats (Contente, Stefanoni, & Spach, ); spatial segregation between gobies based on their vulnerability to predation has been documented by Leitão et al. () who reported that smaller individuals frequently use sheltered habitats in a Portuguese estuary.…”
Section: Discussionmentioning
confidence: 93%
“…Previous research on goby ( Ctenogobius sp.) diet indicated that the most important prey items were diatoms growing on seagrass leaves or mudflats (Contente, Stefanoni, & Spach, ); spatial segregation between gobies based on their vulnerability to predation has been documented by Leitão et al. () who reported that smaller individuals frequently use sheltered habitats in a Portuguese estuary.…”
Section: Discussionmentioning
confidence: 93%
“…Only one species has been described until now, Monokalliapseudes schubarti (Mané-Garzón, 1949), distributed from southeastern Brazil to Uruguay (Drumm & Heard 2011, Freitas-Júnior et al 2013. It has been shown to be an important component of estuaries in southern Brazil, where it can reach high population densities and is a major food item of fish, crustaceans, and birds (Bemvenuti 1987, Leite 1995, Rosa-Filho & Bemvenuti 1998, Montagnolli et al 2004, Ferreira et al 2005, Barreiros et al 2009, Contente et al 2009, 2012.…”
mentioning
confidence: 99%
“…Transformações (ln x +1) foram efetuadas para manutenção da linearidade (Legendre & Legendre 1998;Anderson et al, 2008). O efeito dos preditores do modelo mais parcimonioso na estruturação da assembleia foi avaliada através de projeções dos dois primeiros eixos dbRDA (Anderson et al, 2008 (Jaureguizar et al, 2004), seleção específica do habitat para reprodução (Rooper et al, 2005), proteção (Laegdsgaard, & Johnson, 2001), alimentação (Scharf et al, 2004;Contente et al, 2012) e ótimos osmorregulatórios (Rocha et al, 2005) são exemplos de processos biológicos expressos por distância e gradientes de tipos e diversidade de habitats (Sheaves et al, 2007a), impacto ambiental (Ramos- Miranda et al, 2005), profundidade (Chagas et al, 2006) são exemplos de processos físicos.…”
Section: Identificação Dos Fatores Estruturadores Das Assembleias Do Eciunclassified
“…As relações matemáticas entre a riqueza e a quantidade de organismos provê indicações sobre a 'permeabilidade' do PRE em comunidades locais (Cornell & Lawton,1992;Oberdorff et al, 1998;Cornell, 1999) e, assim, sobre a estrutura da metacomunidade (Leibold et al, 2004;Thrush et al, 2010 (Soares et al, 1993;Wakabara et al, 1993;, Höfling et al, 1998a, Höfling et al, 1998bStefanoni, 2008;Contente et al, 2009;Contente et al, 2010;Contente et al, 2012;Dantas et al, 2013). ER e MM devem ter vantagens na competição por espaço e alimento, porque possuem maior adaptação às condições estuarinas do que as colonizadoras (Sosa-Lopez et al, 2007;Mouillot, 2007).…”
Section: Relação Entre Riqueza E Densidade Na Baía Do Trapandéunclassified
See 1 more Smart Citation